2016
DOI: 10.1097/aog.0000000000001717
|View full text |Cite
|
Sign up to set email alerts
|

Readmission and Prolapse Recurrence After Abdominal and Vaginal Apical Suspensions in Older Women

Abstract: Objective Our objective was to evaluate 30-day readmission, 12-month prolapse recurrence, and complications after apical surgeries in older women. Methods A retrospective cohort study was conducted using 2002–2011 Medicare data in women ≥65 years who underwent abdominal sacrocolpopexy with synthetic mesh, or vaginal uterosacral, or sacrospinous colpopexy with 12-months follow-up. Vaginal mesh procedures were excluded. The primary outcome was 30-day inpatient readmission. Secondary outcomes were complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Fifteen studies including 4,120 cases (2,409 cases for SSLF, 1,439 cases for ASC, and 272 cases for LSC) fulfilled the inclusion criteria and were included in the final analysis (Fig. 1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. All publications were full-text articles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifteen studies including 4,120 cases (2,409 cases for SSLF, 1,439 cases for ASC, and 272 cases for LSC) fulfilled the inclusion criteria and were included in the final analysis (Fig. 1) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. All publications were full-text articles.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included are shown in Table 1. There were 5 RCTs [14,20,21,25,28] (level of evidence: 2b) [29]; 8 retrospective studies [15,16,18,19,22,24,26,27] and 2 prospective studies (level of evidence: 2b-3b) [17,23]. As for surgical procedures, 10 studies compared SSLF with ASC [15,16,18,[20][21][22][23][24][25]28] [14,17,19,26], and 1 compared ASC, LSC, and SSLF [27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 6 Some studies have focused on resumption time, frequency of sexual intercourse and influence of fatigue on sexual intercourse. 7 8 At present, the guidelines for clinical postpartum contraception recommend the initiation of effective contraception 3 weeks after delivery to avoid short pregnancy intervals. 9 Decllines in unintended pregnany rates in Africa and in Western regions are attributed to implementation of family planning.…”
Section: Introductionmentioning
confidence: 99%